Tinjauan Yuridis Pemberian Grasi Oleh Presiden Terhadap Terpidana Kejahatan Narkotika Menurut Hukum Positif di Indonesia - Mahasena, Adhyaksa; Walesa Putra, I Made (Kertha Wicara : Journal Ilmu Hukum; Vol. 01, No. 03, Juli 2013, 2013)
Narcotics crime is a crime that is growing very rapidly along with thedevelopment of social and economic life of the international community, which is verydetrimental to state crime and society itself. But the trouble is that when the polemics ofgranting clemency to convicted narcotics President made widely public tantrum. Oneside of the apparatus to work with communities to fight drug trafficking, but on theother hand the specific reasons need to forgiveness as outlined in the clemency decision.
Keywords: Clemency, President, Crime Narcotics, Public